THE IMPACT OF INSURANCE AGENT’S CREDIBILITY TO CUSTOMER’S ATTITUDE IN BUYING POLICY - Prihatiningsih, Witanti; Ayuningtyas, Fitria (International Journal of Psychosocial Rehabilitation, 2020)
Companies must have their own criteria for their sales agents, start from how to speak in front of potential customers, personal appearance and knowledge about the products and the company itself. The credibility of sales agents will make their companies have a good reputation. Insurance agents also trained by company to introduce the products until someone willing to buy the products and become their loyal customer. This research aims to determine whether there is any significant impact of insurance agent’s credibility to customer’s attitude in buying a policy. The long-term results of the research can be used as communication competence for agents to persuade potential customers, who probably initially not interest to buy the products, became a loyal customer. This research used combination between quantitative and qualitative research. This research used regression analysis to determine the impact of insurance agent’s credibility to customer’s attitude in buying policy and combine with triangulation data from qualitative perspective. The data collection techniques used questionnaires that distributed to the respondent and in-depth interview for key informant and informant(s). The respondent of this research were people who have insurance in the city of Sukabumi, West Java. The theory that used in this research was source credibility and customer’s attitude. The results of this research indicate that trustworthiness, expertise, and attractiveness of insurance agents have a significant impact to customer’s attitude in buying a policy. From the three components, the most important thing is the expertise. The expertise of insurance agent has a highest score compare with trustworthiness and attractiveness of insurance agent and thru in-depth interview, the respondent agreed that expertise is the important things of insurance agent’s credibility. This proves that the agent's expertise is more influential compared to trustworthiness and attractiveness.